The role of tumor metabolism as a driver of prostate cancer progression and lethal disease: results from a nested case-control study. Issue 1 (December 2016) - Kelly, Rachel; Sinnott, Jennifer; Rider, Jennifer; Ebot, Ericka; Gerke, Travis; Bowden, Michaela; Pettersson, Andreas; Loda, Massimo; Sesso, Howard; Kantoff, Philip; Martin, Neil; Giovannucci, Edward; et al.
Abstract Background Understanding the biologic mechanisms underlying the development of lethal prostate cancer is critical for improved therapeutic and prevention strategies. In this study we explored the role of tumor metabolism in prostate cancer progression using mRNA expression profiling of seven metabolic pathways; fatty acid metabolism, glycolysis/gluconeogenesis, oxidative phosphorylation, pentose phosphate, purine metabolism, pyrimidine metabolism and the tricarboxylic acid cycle. Methods The study included 404 men with archival formalin-fixed, paraffin-embedded prostate tumor tissue from the prospective Health Professionals Follow-up Study and Physicians' Health Study. Lethal cases (n  = 113) were men who experienced a distant metastatic event or died of prostate cancer during follow-up. Non-lethal controls (n  = 291) survived at least 8 years post-diagnosis without metastases. Of 404 men, 202 additionally had matched normal tissue (140 non-lethal, 62 lethal). Analyses compared expression levels between tumor and normal tissue, by Gleason grade and by lethal status. Secondary analyses considered the association with biomarkers of cell proliferation, apoptosis and angiogenesis. Results Oxidative phosphorylation and pyrimidine metabolism were identified as the most dysregulated pathways in lethal tumors (p  < 0.007), and within these pathways, a number of novel differentially expressed genes were identified includingPOLR2K andAPT6V1A . The associations were tumor specific as there was no evidence any pathways were altered in the normal tissue of lethal compared to non-lethal cases. Conclusions The results suggest prostate cancer progression and lethal disease are associated with alterations in key metabolic signaling pathways. Pathways supporting proliferation appeared to be of particular importance in prostate tumor aggressiveness.